EXPLORING ENTREPRENEURIAL PERCEPTION AND CHALLENGES OF AFRICAN STUDENTS ABROAD: THE CASE OF MACAU. - Fati, Mamadu (2025)
This paper explores the entrepreneurial perception and challenges of African students from Portuguese-speaking countries (PSC) in Macau, adopting a qualitative research method and conducting in-depth interviews with ten students from this geographic area to understand their Perceptions and challenges towards the entrepreneurial field. This study is significant because it enriches the theoretical guidance framework. Moreover, it helps future researchers utilize valuable data for their research in the field with many samples. The insights obtained from this paper might inform policymakers and universities about the necessary framework to support international students, especially African students from Portuguese-speaking countries, in a way that can encourage them to pursue entrepreneurial opportunities. In-depth interviewing is the primary method for data collection. The thematic content analysis (TCA) An approach is utilized to analyze the data from interview transcripts. Existing research illustrated students from this geographic area's entrepreneurial perception and challenges, as well as their aspirations and intentions as planned after their study. From the point of view of the researcher's interview with his sources, the researcher discovered that there is no opportunity for them to pursue an entrepreneurial career in Macau, which means that, after their study, they will return to their motherland. III In conclusion, based on the findings, understanding the entrepreneurial perception and challenges Students from this geographic area can help to provide support from the local Government and Universities, based on their field of study in a way they can have the opportunity to explore practical experience in a working environment for their personal and professional development.